2016
DOI: 10.1152/jn.00188.2016
|View full text |Cite
|
Sign up to set email alerts
|

Associative spike timing-dependent potentiation of the basal dendritic excitatory synapses in the hippocampus in vivo

Abstract: Spike timing-dependent plasticity in the hippocampus has rarely been studied in vivo. Using extracellular potential and current source density analysis in urethane-anesthetized adult rats, we studied synaptic plasticity at the basal dendritic excitatory synapse in CA1 after excitation-spike (ES) pairing; E was a weak basal dendritic excitation evoked by stratum oriens stimulation, and S was a population spike evoked by stratum radiatum apical dendritic excitation. We hypothesize that positive ES pairing-genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…After exposing the skull, bilateral holes of ~1 mm were drilled, using a mouse atlas (Franklin & Paxinos, ) for placement of stimulating electrodes (Figure ) at (a) medial perforant path (MPP) (anterior/posterior (A/P): −4.1 mm; medial/lateral (M/L): ±2.3 mm; depth (D) from the skull surface: ~1.4 mm), (b) CA3 stratum oriens (OR) (A/P: −2.2 mm; M/L: ±2.5 mm; D: ~1.4 mm), or (c) CA3 stratum radiatum (RAD) (A/P: −2.2 mm; M/L: ±2.5 mm, D: ~1.8 mm). Each stimulating electrode was a Teflon‐insulated stainless‐steel wire with an inner diameter of 127 μm, and the depth of the electrode was optimized to give the lowest threshold of the known pattern of electrophysiological response as illustrated here and previously (Fung, Law, & Leung, ; Hutchison, Chidiac, & Leung, ). A recording probe was placed in CA1, at position A/P: −2.2 mm; M/L: ±1.4 mm for CA3 Schaffer collaterals activation by OR or RAD stimulation, or at a more posterior position (A/P: −3.2 mm; M/L: ±2.8 mm) for temporoammonic‐CA1 activation by MPP stimulation.…”
Section: Methodsmentioning
confidence: 99%
“…After exposing the skull, bilateral holes of ~1 mm were drilled, using a mouse atlas (Franklin & Paxinos, ) for placement of stimulating electrodes (Figure ) at (a) medial perforant path (MPP) (anterior/posterior (A/P): −4.1 mm; medial/lateral (M/L): ±2.3 mm; depth (D) from the skull surface: ~1.4 mm), (b) CA3 stratum oriens (OR) (A/P: −2.2 mm; M/L: ±2.5 mm; D: ~1.4 mm), or (c) CA3 stratum radiatum (RAD) (A/P: −2.2 mm; M/L: ±2.5 mm, D: ~1.8 mm). Each stimulating electrode was a Teflon‐insulated stainless‐steel wire with an inner diameter of 127 μm, and the depth of the electrode was optimized to give the lowest threshold of the known pattern of electrophysiological response as illustrated here and previously (Fung, Law, & Leung, ; Hutchison, Chidiac, & Leung, ). A recording probe was placed in CA1, at position A/P: −2.2 mm; M/L: ±1.4 mm for CA3 Schaffer collaterals activation by OR or RAD stimulation, or at a more posterior position (A/P: −3.2 mm; M/L: ±2.8 mm) for temporoammonic‐CA1 activation by MPP stimulation.…”
Section: Methodsmentioning
confidence: 99%
“…The rat’s rectal temperature was maintained at 36.5–37°C via feedback heating. Monopolar stimulating electrodes (127-µm diameter stainless steel wire, Teflon-coated except at cut ends) were lowered into RAD at P3.2, L3.2, ventral from skull surface (V) ∼3.0 (all units in mm) and stratum oriens (OR) at P3.2, L2.2, V ∼2.5, with bregma and λ on a horizontal plane (Paxinos and Watson, 1998; Fung et al, 2016). Two screws were secured in the skull over the cerebellum and frontal cortex to serve as the stimulus anode and recording ground.…”
Section: Methodsmentioning
confidence: 99%
“…Cathodal pulses were delivered to the RAD and OR stimulating electrodes, and a stimulating electrode was optimized to evoke apical or basal dendritic responses from CA1 pyramidal cells. A silicon probe with 16 recording sites spaced 50 µm apart on a vertical shank (A1x16-5mm-100-177; NeuroNexus) was lowered into CA1 at P3.8, L2.0, V ∼3.0, to record evoked population EPSPs (pEPSPs; Kloosterman et al, 2001; Fung et al, 2016). Signals from the silicon probe were amplified by a headstage (Tucker-Davis Technologies; TDT) and fed into a Medusa preamplifier and digital processors (RA16 Base Station).…”
Section: Methodsmentioning
confidence: 99%
“…In spike timing-dependent plasticity (STDP), the timing between recorded action potentials and triggered stimulation (i.e., ADS) has been shown to determine the polarity and magnitude (i.e., potentiation or depression) of any change in post-synaptic potentials (Markram et al, 1997;Bi and Poo, 1998;Fung et al, 2016). McPherson et al demonstrated that ADS can induce neural plasticity, with a time delay of ~10 ms, that improves behavioral recovery after SCI by synchronizing ISMS below the injury with the arrival of functionally related volitional motor commands signaled by muscle activity in the impaired forelimb (McPherson et al, 2015).…”
Section: Spike-stimulus Delays During Ads Are Consistent With Stdp-bamentioning
confidence: 99%
“…The direction of synaptic change is strongly associated with the temporal coupling between presynaptic spiking and postsynaptic depolarization, with LTP occurring when pre-and postsynaptic activity occur together, and LTD occurring when pre-and postsynaptic activity do not occur together (Lisman, 1989). In addition, in vitro studies have noted an effect due to spike order, with LTP occurring when presynaptic inputs occurred first or were synchronous with postsynaptic spikes, and LTD occurring when presynaptic input followed postsynaptic spikes (Levy and Steward, 1983;Debanne et al, 1994Debanne et al, , 1997Fung et al, 2016). Commonly known as precise timing-and order-dependent plasticity, it has been shown that the sign and magnitude of LTP and LTD depend on the order and timing of pre-and postsynaptic spikes on the 10 ms time scale and that a 10-50 ms time delay increased spiking probability (Gerstner et al, 1996;Markram et al, 1997;Bi and Poo, 1999).…”
Section: Introductionmentioning
confidence: 99%